An english-malay translation memory system - Rahman S.B.Ab.; Aziz N.A.; Solemon B. (2023)
This paper discusses on an English-Malay Translation Memory (TM) prototype system developed as a tool to translate English to Malay text by re-using pre-translated examples stored in the TM repositories. The architectural system design and structural model of the English-Malay TM using Data Flow Diagrams (DFDs) are also described. We then shared the sample of implementation model of the English-Malay TM system that will be evaluated by a group of free-lance translators. Plans of further work are also listed in concluding this paper. 2008 IEEE. DOI 10.1109/CIT.2008.Workshops.113.